End to informality? Examining the impact of institutional reforms on informal institutions in post-Euromaidan Ukraine. (1st September 2016) - Aliyev, Huseyn
Abstract: What happens to informal institutions in the process of institutional reforms? This article aims to examine one particular aspect of the complex interaction between institutional reforms and informality; the impact of reforms on informal political institutions. The success of Ukraine's Euromaidan in overthrowing the autocratic government of Viktor Yanukovich in 2014 has ushered a wind of change into the post-Soviet political landscape, for decades dominated by authoritarian and semi-authoritarian forms of governance and the reliance on informal institutions engraved in political traditions. This study is among the first to question as to whether an ambitious reform agenda currently being implemented by the Ukraine's post-Euromaidan government has had a notable impact on the deeply rooted informal relations in the political sphere. Drawing its empirical insights from a series of in-depth interviews conducted in Kiev in 2015, this study shows that while informal relations have become increasingly vulnerable to formalization efforts and, as a result, various informal institutions in present-day Ukrainian politics have lost their functions and influence, other informal institutions are not only being preserved by the political elites, but also are being employed to promote the reform processes.